Pengembangan Aplikasi Smartphone berbasis Android sebagai Penunjang Pembelajaran Mata Pelajaran Fisika untuk SMA Islam As-Syafi'iyah 01 Jakarta (Current Research in Education: Conference Series Journal, 2022)
There are two very important aspects in the world of learning, namely learning methods and learning media as teaching aids. Learning media with android-based technology helps students who are required to learn more independently because the number of hours face to face with the teacher in the classroom is quite limited. However, based on the observations of researchers from industrial practice in 2020 that Islamic Senior High School As-syafi'iyah 01 Jakarta still only uses LCD projector technology as a medium in delivering learning, the use of this media in general has not been able to train students' ability to learn independently. Based on this, to support student learning so that they can train students' ability to learn independently, researchers conducted research on developing android applications as a support for learning physics subjects at Islamic Senior High School As-syafi'iyah 01 Jakarta with using the Research and Development (R D) method which adapted from the ADDIE development model. The results of the study resulted in an Android-based learning media application for physics subjects. The results obtained are expected to be used as further research in testing the feasibility of implementing learning media.